Detection of High-Grade Prostate Cancer among PLCO Participants Using a Prespecified Four Kallikrein Marker Panel - Kim, Eric H. (J Urol, 2016)
PURPOSE: To assess the performance of a four-kallikrein panel, with and without microseminoprotein-beta (MSP), to predict high-grade (Gleason 7+, Gleason Grade Group 2+) prostate cancer (PCa) on biopsy in a multiethnic cohort from the Prostate, Lung, Colorectal, and Ovarian (PLCO) cancer screening trial. MATERIALS AND METHODS: Levels of free, intact, total prostate-specific antigen (PSA), human kallikrein-2, and MSP were measured blinded to outcome in cryo-preserved serum from men in the intervention arm of PLCO. Marker levels from 946 men, of whom 100 were African-American, were incorporated into a prespecified statistical model to predict high-grade PCa on biopsy. RESULTS: The detection of high-grade PCa (n=94, 10%) was enhanced by the four-kallikrein panel with an AUC of 0.79 compared to 0.73 for the Prostate Cancer Prevention Trial (PCPT) risk calculator (increase of 0.060; 95% C.I. 0.032, 0.088; p<0.01). Additionally, the AUC increased from 0.79 to 0.81 when MSP was added to the four-kallikrein panel. In African-American men, the four-kallikrein panel model also enhanced high-grade PCa detection over PSA (AUC 0.80 versus 0.67). As an illustration of clinical implications, use of one cut-point for biopsy (6% risk of high-grade PCa) with the four-kallikrein panel model would have eliminated unnecessary biopsies in 42% (397/946) of our cohort while detecting 88% (83/94) of highgrade PCa. CONCLUSIONS: In a multiethnic United States population, the four-kallikrein panel demonstrates improved risk discrimination for high-grade PCa over conventional clinical variables (age, PSA, digital rectal examination) as well as the PCPT risk calculator.